Modulation of Kv11.1 (hERG) channels by 5‐(((1H–indazol‐5‐yl)oxy)methyl)‐N‐(4‐(trifluoromethoxy)phenyl)pyrimidin‐2‐amine (ITP‐2), a novel small molecule activator. (18th June 2017) - Sale, Harinath; Roy, Samrat; Warrier, Jayakumar; Thangathirupathy, Srinivasan; Vadari, Yoganand; Gopal, Shruthi K; Krishnamurthy, Prasad; Ramarao, Manjunath
Abstract : Background and Purpose: Activators of Kv 11.1 (hERG) channels have potential utility in the treatment of acquired and congenital long QT (LQT) syndrome. Here, we describe a new hERG channel activator, 5‐(((1H–indazol‐5‐yl)oxy)methyl)‐N‐(4‐(trifluoromethoxy)phenyl)pyrimidin‐2‐amine (ITP‐2), with a chemical structure distinct from previously reported compounds. Experimental Approach: Conventional electrophysiological methods were used to assess the effects of ITP‐2 on hERG1a and hERG1a/1b channels expressed heterologously in HEK‐293 cells. Key Results: ITP‐2 selectively increased test pulse currents (EC50 1.0 μM) and decreased tail currents. ITP‐2 activated hERG1a homomeric channels primarily by causing large depolarizing shifts in the midpoint of voltage‐dependent inactivation and hyperpolarizing shifts in the voltage‐dependence of activation. In addition, ITP‐2 slowed rates of inactivation and made recovery from inactivation faster. hERG1a/1b heteromeric channels showed reduced sensitivity to ITP‐2 and their inactivation properties were differentially modulated. Effects on midpoint of voltage‐dependent inactivation and rates of inactivation were less pronounced for hERG1a/1b channels. Effects on voltage‐dependent activation and activation kinetics were not different from hERG1a channels. Interestingly, hERG1b channels were inhibited by ITP‐2. Inactivation‐impairing mutations abolished activation by ITP‐2 and led to inhibition of hERG channels. ITP‐2 exerted agonistic effect from extracellular side of the membrane and could activate one of the arrhythmia‐associated trafficking‐deficient LQT2 mutants. Conclusions and Implications: ITP‐2 may serve as another novel lead molecule for designing robust activators of hERG channels. hERG1a/1b gating kinetics were differentially modulated by ITP‐2 leading to altered sensitivity. ITP‐2 is capable of activating an LQT2 mutant and may be potentially useful in the development of LQT2 therapeutics.